(3TQM bhGYO GdCMcGe aj eYQaI GdMdGd hGdMQGe s - (3eLghds ((3GHf edG bGSe eMeO UGdM GdTgQRGOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bhdg cJGH GdeJGLQ gjeY eJLQ gh EeG eUOQ ejej HeYfi GdJLGQI cGdebJd HeYfi GdbJd s
(3BNQgG (B:s
(3aEfg EPG de jcf eGdcG de jcf gfGc HjY hCeG Ef faj OYhGg Yf faSg abW hde jJYQV dfaj CUd Gdec aEfg jSJMb GdTaYI dMUhd GdebJVis
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3abg GdePGgH GdCNQis